NUMERICAL AND EXPERIMENTAL INVESTIGATIONOF STEAM FILM CONDENSATION ON A VERTICAL TUBE (Journal of Engineering, 2024)
Film condensation of steam on a vertical tube is investigated numerically and experimentally, in the present work. A mathematical model was set based on the basic conservation laws of mass and energy, Nusselts analysis of film condensation, and empirical equations available in the literature. Then, a simulation program in FORTRAN language was developed which simulates the film condensation of steam on a vertical tube. A complete steam tables subprogram was also developed and incorporated with the main program. The experimental work was carried out using a steam condensation test bench. The inlet and outlet cooling water temperatures, steam temperature and pressure, tube surface temperature at center, and cooling water flow rate are recorded during each experimental test run. The inlet cooling water temperature, steam temperature, and cooling water flow rate are used as an input for the numerical program, then the program calculates tube surface temperature distribution, cooling water temperature distribution, local heat transfer rate, local condensation heat transfer coefficient, condensate boundary layer thickness distribution, total heat transfer rate, and average condensation heat transfer coefficient. The effect of various parameters on the condensation heat transfer coefficient, such as steam temperature, steam-surface temperature difference, and the presence of non-condensable gas were investigated and reported graphically. It was found that increasing (steam-surface) temperature difference while keeping the steam temperature constant results in an increase in condensate boundary layer thickness, which in turn causes a decrease in condensation heat transfer coefficient. On the other hand, increasing steam temperature and keeping the (steam-surface) temperature difference constant leads to an increase in condensation heat transfer coefficient. In addition, the presence of non-condensable gas with different concentrations was also investigated and it was shown that it causes a noticeable reduction in the average condensation heat transfer coefficient. An equation for calculating average condensation heat transfer coefficient on a vertical tube was also developed. The experimental data obtained from the test runs were compared with numerical results and showed good agreement. Thus, it can be concluded that the present computational program is suitable for simulating steam condensation on a vertical tube.